Seeking Stanislavski Techniques of Actor Training in Nepalese Context from His Book An Actor Prepares - Karki Kshetri, Dibendra Bahadur (Journal of Development and Social Engineering, 2022)
This paper aims at searching for techniques of actor training in Nepal associating similarities (or differences if any) theorized by Constantin Stanislavski (1863-1938), a Russian theatre director in his book An Actor Prepares. The acting ‘system’ also known as ‘method’ is an approach to acting, developed in the 1920s to support actors in the process of embodying and enacting a role. Although acting may not be an exact science, there is a method to the madness as the package of three-month actor training in Nepali Acting Schools (Gurukul, Actor’s Studio, Mandala, and Sarwanam) like Stanislavski’s. When the body is true, the soul reacts. When the body lies, the soul gets frightened. Where there is truth and belief, actors have genuine, productive, specific action, experiences, the subconscious, creativity and art. Actors communicate others in creative and convincing ways. People look for creative instincts, innate talent, and intellectual capacity to perform. Performance, connected to everyday life, is both believing and living. Theatre/Film has been considered as an important platform to showcase socio-political, eco-cultural or historic- religious realities in Nepal.